Analytic, Real Analytic and Harmonic Generalized Functions - Pilipović, S. (Sarajevo Journal of Mathematics, 2024)
We recall definitions and assertions concerning the spaces noted in the title. Various classes of nonlinear problems can be studied within these spaces appropriate for the analysis of different kinds of singularities. Especially, we explain in this paper the notion of the generalized analytic wave front set. 2000 Mathematics Subject Classification. 46F10, 46S10, 35A27